Exploring The Challenges of Disabled Entrepreneurs: A Literature Study - Muhammad Firdaus bin Muhammad Sabri; Salina Mohammed Rashid; Suhaila binti Nadzri (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Self-employment or engaging in the world of entrepreneurship is a traditional career for people with disabilities (PWDs) to earn a living due to the difficulty of finding job. In the current scenario, there are many studies related to disabled entrepreneurs that have been conducted. However, components that related to the entrepreneurial challenges faced by this group is still new and needs to be studied in depth. Identifying key challenges is important for entrepreneurs with disabilities to enable them to strategize, set priorities and identify support systems that can help them survive. In relation to that, the purpose of this article is to discuss the anticipated challenges from previous studies related to entrepreneurship among PWDs. Several articles were selected and analysed from two databases; namely Scopus and Google Scholar. The data obtained are grouped into a thematic form. The data obtained was categorized into two types, namely external challenges and internal challenges. Based on the findings of this article, there are two main factors related to the challenges of entrepreneurship with the disabled, which are internal factors and external factors. The internal factors are divided into two, namely personal factors and self-resilience. While the external factors that give challenges to entrepreneurs with disabilities are divided into three, namely discrimination, financial factors and the environment. This article is expected to be able to contribute to government policy, especially for interested parties to find alternatives in increasing the involvement of this group in entrepreneurial activities. It is also suggested that the government improve the existing support system so that these disabled etrepreneurs can be competitive and lessen the problems that they face.